A Study on Higher Education Student Satisfaction and Educational Marketing in Peru - Laura-De La Cruz, Kevin Mario; Bahamondes-Rosado, María Emilia; Velarde-Molina, Jehovanni Fabricio; Laura-De La Cruz , Bianca Daisa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this research was to determine the relationship between educational marketing and student satisfaction in Higher Education Institutions in the Tacna region, in order to analyse the characteristics that are related to the study variables. The methodology was carried out under a quantitative approach, with a correlational and transversal research design; sample was composed of 249 students. Pearson's statistical test was applied, showing that the educational marketing variable is significantly related to student satisfaction in higher education institutions. Finally, it was demonstrated that the students evidenced effective characteristics of their respective institutions that differentiate them from others.